Gender Gap in Attitudes towards Science and STEM areas in Lower Secondary Students - Grassi, Lubiana; Garcia De Cajen, Silvia (LACCEI, 2024)
Attitudes toward science are a topic of growing interest in science education research, particularly due to their impact on the underrepresentation of women in STEM fields. Understanding the factors that influence these attitudes is crucial, especially in the 13-14 age group, where the literature indicates a decline in favorable attitudes. This study aims to identify the existence of a gender gap in attitudes toward science and STEM fields among first- and second-year Lower Secondary students at the Ernesto Sábato National School (ENES) in Tandil, Argentina. The study considers the dimensions of the social relevance of science, taste for science, interest in scientific topics, professional interest in science, and desire to pursue STEM careers. A non-experimental cross-sectional design and quantitative methodology are applied, using Likert scale questionnaires and open questions to provide qualitative information about the phenomenon. The results show that the gender gap in attitudes toward science and STEM fields becomes significant in the second year, with female students showing a marked unfavorable trend in terms of enjoyment of school science, interest in scientific topics, and desire of pursuing STEM careers compared to their male counterparts. This suggests that the way science is presented and perceived at the beginning of high school affects students' attitudes and creates an unfavorable biographical profile.